Levels of second hand smoke in pubs and bars by deprivation and food-serving status: a cross-sectional study from North West England - Hart Judy; Holford Richard; Probert Claire; Hargreaves Kim; Hasselholdt Christian P; Edwards Richard; Van Tongeren Martie; Watson Adrian FR (BMC, 2006)
Abstract Background The UK government proposed introducing partial smokefree legislation for England with exemptions for pubs and bars that do not prepare and serve food. We set out to test the hypothesis that pubs from more deprived areas and non food-serving pubs have higher levels of particulate air pollution. Methods We conducted a cross sectional study in four mainly urban areas of the North West of England. We recruited a stratified random sample of 64 pubs divided into four groups based on whether their local population was affluent or deprived (using a UK area based deprivation measure), and whether or not they served food. The timing of air quality monitoring stratified to ensure similar distribution of monitoring by day of the week and time of evening between groups. We used a portable air quality monitor to collect fine particle (PM2.5) levels over a minimum of 30 minutes in areas where smoking was allowed,, and calculated mean time-time weighted average PM2.5 levels. Results Mean PM2.5 was 285.5 μg/m3 (95% CI 212.7 to 358.3). Mean levels in the four groups were: affluent food-serving pubs (n = 16) 188.1 μg/m3 (95%CI 128.1 to 248.1); affluent non food-serving (n = 16) 186.8 μg/m3 (95%CI 118.9 to 254.3); deprived food-serving (n = 17) 399.4 μg/m3 (95%CI 177.7 to 621.2); and deprived non food-serving (n = 15) 365.7 μg/m3 (195.6 to 535.7). Levels were higher in pubs in deprived communities: mean 383.6 μg/m3 (95% CI 249.2 to 518.0) vs 187.4 μg/m3 (144.8 to 229.9); geometric mean 245.2 μg/m3 vs 151.2 μg/m3 (p = 0.03). There was little difference in particulate levels between food and non food-serving pubs. Conclusion This study adds to the evidence that the UK government's proposals for partial smokefree legislation in England would offer the least protection to the most heavily exposed group - bar workers and customers in non food-serving pubs in deprived areas. The results suggest these proposals would work against the UK government's stated aim to reduce health inequalities.